HIGH SACRAL HIATUS WITH NON FUSION OF LAMINA OF FIRST SACRAL VERTEBRAE: A CASE REPORT - Vishal, K.; V., Vinay K.; K., Remya; Kumar, Arunachalam; K., Shishir (Journal of Health and Allied Sciences NU, 2012)
Sacrum is a large triangular bone, forming postero-superior wall of the pelvic cavity. During the routine study of bones in the department of Anatomy, an unusual variation in the sacrum was noted. The bone showed high sacral hiatus i.e., at the level of 3rd sacral vertebrae and non-fusion of lamina of 1st sacral vertebrae This type of anomaly is very rare, which prompted us to report the case. The knowledge about this rare variation is important for orthopaedicians and anesthetists since the high sacral hiatus may lead to clinical procedural failures. It is also important for accurate diagnosis of patients with low back pain. Non-fusion of lamina of 1st sacral vertebrae may be associated with spina bifida occulta and may lead to painful condition of back.
Keywords: Vertebrae; Sacral Hiatus; Low back pain